Bersih Tanpa Asap: Mahasiswa KKN-T UMSIDA Ciptakan Tong Sampah Inovatif untuk Masa Depan Hijau - Muhammad Triza Rinnuddin; Noor Achmad Rizky Ardhyansyah; Muhammad Rafii; Ferry Adhi Dharma (Lembaga Pengembangan Kinerja Dosen, 2025)
The management of household waste remains a major challenge in society, especially in densely populated rural and urban areas. The practice of open burning of waste is still often carried out because it is considered quick and practical, despite its negative impacts on health and the environment. The smoke from burning can trigger respiratory diseases, reduce air quality, and accelerate global warming. In light of this issue, the 2025 KKN-T 23 UMSIDA students initiated a community service program by introducing an innovation in the form of an environmentally friendly waste bin that can reduce the practice of waste burning. This waste bin is designed with a system for separating organic and inorganic waste and special ventilation that accelerates the natural decomposition process. Through a participatory approach, students involve the community in the planning, creation, and testing of the innovative trash bins. The results of the activities show an increase in community awareness in sorting waste, a decrease in the habit of burning waste, and an improvement in the quality of the surrounding environment. This program has also successfully fostered collaboration between students, village officials, and residents in creating a greener and healthier environment. This trash bin innovation is hoped to be a sustainable model that can be implemented in various areas as a simple yet effective solution for community-based waste management.